How do school-related mathematical problems become relevant for prospective teachers in mathematics courses at university? A qualitative interview study - Weber, Birke Johanna; Breuer, Jana; Lindmeier, Anke (Research in Mathematics Education, 2023)
Prospective mathematics teachers often have to attend courses in academic mathematics. However, many struggle to see the connections between the course content and their future teaching, which is detrimental to learning motivation and success. Many universities try to address this with interventions focusing on the relevance of the mathematical learning opportunities. School-related mathematical problems (SRMPs), which highlight connections between school mathematics and academic mathematics, are a suggested intervention. Since SRMPs focus on the demands of the future profession, one would expect that students attribute high relevance to them. However, empirical results on this remain limited. To evaluate and enhance SRMPs, our study aims to elicit the criteria students use for assessing the relevance of SRMPs. We analysed ten qualitative interviews with prospective teachers. Our results show that similar criteria determine the perceived relevance in all cases. We discuss practical consequences for the design of school-related learning opportunities in teacher education.
CRIS-Team Scopus Importer:2024-10-02
Keywords: qualitative study; Teacher education; tertiary mathematics